POTENSI OBJEK WISATA SERIBU RUMAH GADANG DI KECAMATAN SUNGAI PAGU KABUPATEN SOLOK SELATAN - Saputra, Ega - (Pendidikan Geografi, 2014)
The problem in this research is the development of cultural attractionsConstraints Thousand region is yet recorded Tower House Tower Houseownership in the region. The purpose of this study is to describe the potential,strategy development and problems were found in the development of a Thousandattraction Tower House in Sungai Capping South Solok. The research is aqualitative research. This research was conducted at Sungai Capping South Solokof West Sumatra. The type of data in this study are primary and secondary data.According to the type of data collected in this study, the primary data source isthe respondent in the field and secondary data obtained from the BPS TourismOffice, Head Office, and relevant agencies. Data collection techniques in thisstudy is the interview.